The influence of emotions and learning preferences on learning strategy use before transition into high-achiever track secondary school. (2nd January 2016) - Obergriesser, Stefanie; Stoeger, Heidrun
Abstract : Research on the relationships between students' achievement emotions and their (self-regulated) learning behavior is growing. However, little is known about the relationships between students' learning preferences and achievement emotions and the extent to which these influence learning strategies. In this study we, first, looked at the learning-style preferences (self-regulated, externally regulated, or impulsive learning) of 200 fourth graders who were about to start high-achiever track secondary school in Germany in the following school year. Second, we analyzed whether students who prefer self-regulated learning, externally regulated learning, or impulsive learning differ concerning the achievement emotions of enjoyment, anger, boredom, and anxiety. Third, we examined whether the degree to which students prefer self-regulated learning in combination with their achievement emotions predicts if and how students actually apply various aspects of self-regulated learning such as cognitive learning strategies, goal setting, and strategy monitoring during their learning. Fourth, we explored whether achievement emotions mediate relationships between more or less successful learning and subsequent learning behavior. Students in our sample did not prefer a self-regulated learning style over an externally regulated or impulsive learning style; and achievement emotions were shown to be related to students' learning-style preferences. Students' preference for self-regulated learning in combination with their achievement emotions predicted various aspects of their learning. However, achievement emotions did not mediate changes in learning behavior found after less successful learning.